+0  
 
+5
622
1
avatar
Show step by step solving

y= 1/2x - 6
2x + 6y= 19

using elimination method.

Then show step by step solving
y= 1/2x - 6
2x + 6y= 19

using graphing method.
Guest Jan 30, 2012
 #1
avatar+3077 
0
[input]solve( y= 1/(2x) - 6, 2x + 6y= 19 )[/input]

y= 1/(2x) - 6
2x + 6y= 19

2x + 6*(1/(2x) - 6)= 19
2x + 6/(2x) - 36= 19 |+36
2x + 6/(2x) = 19+36
2x + 6/(2x) = 55 | *2x
(2x)^2 + 6 = 110x | -6 , -110x
(2x)^2 - 110x = -6 | +6
4x^2 - 110x + 6 = 0
=>
x=-(1/4*sqrt(3001))+54/4)
x=1/4*sqrt(3001)+55/4

insert into y= 1/(2x) - 6
y=-(1/12*sqrt(3001))-17/12
y=1/12*sqrt(3001)-17/12
admin  Jan 31, 2012

10 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.